The decentered translation of management ideas: Attending to the conditioning flow of everyday work practices - Hultin, Lotta; Introna, Lucas D; Mähring, Magnus (Human relations (New York), 2021)
Based on a study of Lean management practices at the Swedish Migration Board, we develop a novel theoretical understanding of the translation of management ideas. We show how translation, rather than being reduced to a network of human intentions and actions governing the transformation of organizational practices, can instead be understood as a historically contingent, situated flow of mundane everyday work practices through which social and material translators simultaneously become translated, conditioned to be and act in certain ways. We show how prior actor-centric accounts of translation of management ideas can be understood as performative consequences of a conceptual vocabulary inherited from Callon and Latour. Contrasting this, the non-actor-centric vocabulary of social anthropologist Tim Ingold allows us to background the intentional human actor and foreground the flow of mundane, situated practices. In adopting this vocabulary, we capture how the flow of practices conditions subjects and objects to become enacted as well as act, and develop an understanding of translation as occurring within, rather than distinct from, these practices. In essence, our novel view of translation emphasizes how management ideas are radically unstable, and subject to alteration through the flow of practices rather than as a result of deliberate implementation efforts.